2016
DOI: 10.1177/0748233716670536
|View full text |Cite
|
Sign up to set email alerts
|

Assessing genotoxicity of diuron on Drosophila melanogaster by the wing-spot test and the wing imaginal disk comet assay

Abstract: The aim of this study was to evaluate the genotoxicity of the herbicide diuron in the wing-spot test and a novel wing imaginal disk comet assay in Drosophila melanogaster. The wing-spot test was performed with standard (ST) and high-bioactivation (HB) crosses after providing chronic 48 h treatment to third instar larvae. A positive dose-response effect was observed in both crosses, but statistically reduced spot frequencies were registered for the HB cross compared with the ST. This latter finding suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…These results could be related to investigations with other types of herbicides performed to test their genotoxicity in the wing spot test: alachlor, atrazine and paraquat were only positive in the ST cross (Torres et al 1992), as well as 2,4,5-trichlorophenoxyacetic acid, maleic hydrazide and glyphosate (Kaya et al 2000b). Recently the phenyl-urea herbicide diuron, chemically related to linuron, has been shown to induce similar results in the wing spot test of Drosophila: a positive dose-response effect in the ST cross while only positive at the highest concentration in the HB cross (Peraza-Vega et al 2016). Additionally, the genotoxic effect detected for diuron in the wing spot test was related by these authors to the DNA damage induced in the wing imaginal disk comet assay.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…These results could be related to investigations with other types of herbicides performed to test their genotoxicity in the wing spot test: alachlor, atrazine and paraquat were only positive in the ST cross (Torres et al 1992), as well as 2,4,5-trichlorophenoxyacetic acid, maleic hydrazide and glyphosate (Kaya et al 2000b). Recently the phenyl-urea herbicide diuron, chemically related to linuron, has been shown to induce similar results in the wing spot test of Drosophila: a positive dose-response effect in the ST cross while only positive at the highest concentration in the HB cross (Peraza-Vega et al 2016). Additionally, the genotoxic effect detected for diuron in the wing spot test was related by these authors to the DNA damage induced in the wing imaginal disk comet assay.…”
Section: Resultsmentioning
confidence: 92%
“…This cytotoxicity was accompanied by the induction of single-strand breaks in liver as seen by the alkaline elution assay (Scassellati-Sforzini et al 1997). Diuron, also a phenyl-urea herbicide as linuron, showed to induce sex-linked recessive lethals in Drosophila melanogaster (Rodríguez-Arnaiz et al 1989) and recently has been shown to be genotoxic in the wing spot assay and in a new developed wing disk comet assay demonstrating a positive correlation between both assays (Peraza-Vega et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The use of Drosophila melanogaster in toxicological studies has increased [4252] given the genome of flies has homology to the human genome [53], thus making it a highly predictive model of toxicity in vertebrates. D. melanogaster has numerous thiol-containing proteins involved in redox signaling [54] and five selenoproteins [55–59].…”
Section: Introductionmentioning
confidence: 99%
“…Ricardo Peraza Vega from the same group, headed by Rosario Rodr ıguez Arnaiz, described a new comet assay using cells from the wing imaginal discs of Drosophila larvae to test the toxicity of another herbicide, diuron, which causes DNA breaks observable on the comet assay that could be related to the mutation and recombination events obtained with the classic wing-spot test. 22 The Diana Res endez-P erez lab from the University Autonomous of Nuevo Leon in Monterrey presented novel work on the regulation of Antennapedia (Antp). 23 Asking how different Hox genes acquire their specificity despite their similar DNA homeodomain preferences, Claudia Altamirano Torres showed a physical interaction between Antp and TFIIE-b, implicating this protein-protein interaction during antenna specification in development.…”
Section: Introductionmentioning
confidence: 99%